(untitled) (Medico Legal Update, 2021)
Background: Breast cancer is disease in which cells in breast tissue change and divide uncontrolled, resulting in a lump or mass. This study aims to determine the efficacy of health belief model-based intervention in enhancing women’s breast cancer screening behaviors. Method: A randomized controlled trial was conducted using the Health Belief Model. The study included a systematic random sample of 110 women. Women who age 22-68-years were selected from Banks in AlNajaf Al-Ashraf City. Data were collected through a self-report instrument that includes women’s sociodemographic characteristics of age, marital status, and economic status, the Perceived Susceptibility Scale, the Perceived Benefits Scale, the Self-Efficacy Scale, the Health Motivation, the Perceived Severity Scale, and the Perceived Barriers Scale. Data were analyzedusing the statistical package forsocial sciences, version 26. The study results revealed that HBM-based intervention was efficacious in enhancing the Perceived Susceptibility, the Perceived Benefits, the Self-Efficacy, the Health Motivation, the Perceived Severity, and the Perceived Barriers for women in the study group. The researcher concluded that the HBM-based intervention we as efficacious in enhancing women’s screening behaviors for breast cancer. Conclusion: The researcher concluded that the HBM-based intervention was effective in enhancing women’s breast cancer screening behaviors.